Effect of Work Environment and Teacher’s Motivation on Teacher’s Performance - Octaviani, Gittaria; Fitria, Happy; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study is to ascertain how the work environment, teacher motivation, and supervision affect public elementary school teachers’ performance in Namang District. This kind of study employs an ex post facto research design and is quantitative. Ninety state elementary school teachers in Namang District served as the research sample. This kind of study uses a research strategy and is quantitative. ways for gathering data using surveys. Multiple regression and quantitative descriptive analysis approaches are used in data analysis methods. The study’s findings indicate that: 1) the work environment significantly affects the performance of state elementary school teachers in Namang District; 2) teacher motivation significantly influences the performance of state elementary school teachers in Namang District; and 3) the work environment and teacher motivation significantly jointly affect the performance of state elementary school teachers in Namang District.